FIGURATIVE LANGUAGE SEMANTIC ANALYSIS IN ADHITIA SOFYAN'S ALBUM "Forget YOUR PLAN" - Mawarti, Miya; Laili, Elisa Nurul (Teaching English as Foreign Language, Literature and Linguisticss, 2023)
Figurative language is part of the semantic. As we know that with semantic we can know the true meaning in a song. Figurative language is language which employs various figures as speech. This analyzes the figurative languages are used in Adhitia Sofyan's album â€œForget Your Plansâ€. It is expected that the result of this study will be useful for the student of linguistics since this study is done based on the theory of Figurative Language. The benefit of figurative language and category used in this thesis is that the readers will comprehend that such theory can be used to give clearer and better understanding about the meanings of figurative language. Kind of figurative language was found in Adhitia Sofyan song selected songs lyric are paradox, metaphor, hyperbole, personification, rhetoric, allegory, repetition, and antithesis. Figurative language in the song could make the readers understand that the lyric of the song can describe massages that must be known by learning them deeply in terms of categories. This study attempts to provide a description about figurative language in human daily life. The type of data that is used in this study is a qualitative data. The data analyzed in this study are some written texts. The text discuss is song taken from Adhitia Sofyan's album â€œForget Your Plansâ€. By these classifications, we can recognize well which one includes each figurative speech. The result of this study will be able to give contribution to the readers who are interested in learning